Information System for Bricks Sales Online Based - Linda Wahyuni; Hardianto Hardianto; Rika Rosnelly (JUDIMAS, 2020)
Bricks are a building material that has long been known and commonly used by the community in line with the increasing number and rate of population development. Bricks are materials made of clay with or without additives which go through several processes and stages. The data used in this study is to look directly at the employers and workers who manufacture bricks and look at the various existing literature related to the title that the author studied. The author is interested in researching this stone-making business because to find out how the sales or marketing system for making bricks. From the results of the research conducted by the author, the sales or marketing system for making bricks in Pasar VI village is still done in a simple way, and there is no application. Based on the problems that researchers have observed, an online web-based application is needed so that brick producers can market bricks quickly and earn better profits. This research activity starts from giving directions, providing equipment as sales / marketing aids such as computers, creating websites and training on using the website. The achievement indicators are an increase in partner income by up to 85%, an increase in the amount of production by up to 85%, the partner has a marketing website and can use the website